KONDISI PENDIDIKAN ANAK PADA MASYARAKAT PESISIR (STUDI KASUS DI GILI RE DESA PAREMAS KECAMATAN JEROWARU LOMBOK TIMUR) - Baiq Eka Pratiwi (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2019)
This study aims to determine (1) the condition of children's education in the coastal communities of Gili Re, Paremas Village, Jerowaru District, (2) factors that lead to the continuation of children's education in the coastal communities of Gili Re, Paremas Village, Jerowaru District. This research is a type of descriptive research that is data collected in the form of words rather than numbers. The approach used is a qualitative approach that is a research procedure that produces descriptive data in the form of written or oral words from people and observed behaviors. Data collection techniques namely observation, interviews, documentation. Data analysis uses data reduction, data presentation, drawing conclusions. Education is one of the efforts in order to improve the quality of human life, the problem of education that has not been able to be overcome until now is dropping out of school. Dropouts are those who cannot continue their education due to various factors, the education of children in coastal areas has not been fully considered by the government. The results showed that the education of the children of the coastal communities of Gili Re relied on Gili Beleq because there were no educational facilities on Gili Re. This condition causes children to drop out of school and not continue their education let alone not be fully considered by the government. The compulsory education program set by the government has not been maximized in the Gili Re region. contributing factors to the continuity of children's education in the coastal communities of Gili Re, namely lack of educational facilities, economic conditions of parents, parents and children's views on education still don’t care.